Green hotels: the state of green hotel research and future prospects - Chua, Bee Lia; Han, Heesup (Taylor Francis, 2022)
This paper draws attention to the critical account of green hotels from various stakeholder perspectives. It reviews why and how the green hotel industry is increasingly involved in green initiatives and what results from such efforts, and underpins green sustainability issues ranging from hotel-oriented to individual-oriented factors. How the stakeholders are involved in the process is also observed. There is obvious indication of conservation and pollution management as the mainstream topic in green hotel studies. This paper suggests directions of research in the realm of green hotels, which could serve as a guide for a better conceptualization of future research.